On the Relationship Between the Porosity and Initial Coulombic Efficiency of Porous Carbon Materials for the Anode in Lithium-Ion Batteries - Shaker, Majid; Sadeghi Ghazvini, Ali Asghar; Riahifar, Reza; Mumtaz, Asim (Electronic Materials Letters, 2022)
Herein, we present a new model to investigate the cause of the low initial coulombic efficiency of lithium-ion battery (LIB) porous carbon anodes and discover its relationship with the porosity of these materials. According to the proposed model, the capacity of porous carbon LIB anodes is in a direct relationship with their porosity, which reduces by the formation of the solid electrolyte interphase (SEI) layer occupying the cavities and decreasing the accessible surface area for the electrolyte. The introduced model in this study was compared with the data published in the literature and revealed a satisfactory agreement with them. As a result, it was concluded that the fraction of the mesopores occupied by SEI after the 1st cycle fluctuates around the value of 0.5 and is mostly in the range of 0.6−0.4. Thereby, it can be employed for the prediction of the first cycle coulombic efficiency (CE) of carbonaceous anodes as LIB anodes and optimization of their structure. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-07-01
Keywords: Lithium-ion battery; Modelling; Porous carbon; Solid electrolyte interphase